Musharakah Tijarah cross-border financing: concept, structure and salient features - Salehuddin, Sharullizuannizam; Saiti, Buerhan (PESA Publications, 2016)
Musharakah Tijarah Cross-Border Financing (“Product”) is the product to enable the Bank to undertake project and contract cross-border financing activities or other identified business ventures on “pure” Joint Venture basis,using the underlying Islamic financing contract of Musharakah. Musharakah concept has a low market share of less than 2.5% in the overall existing Islamic financing products in Malaysia. This product encourages mobilization of idle capital / cash entities and thus provides a basis for economic cooperation between these organizations in the society. The product also is expected to inject greater prosper to the Bank’s overall performance and ultimately able to assist small time landowners in a big way through business risk sharing. Musharakah provides an alternative investment, which will cater for Islamic investors and partners, especially from GCC, who may have been reluctant to invest in conventional or current debt-based financing scheme. With Musharakah concept, the most preferred and globally accepted Islamic financing, this can attract these investors to participate on similar risk-sharing arrangements through the creation of Specific Investment Account (SIA) or Islamic Syndication to back financing made into the Joint Venture.